Analysis of the Application of Environmental Accounting in Solid Waste Management in Karawang Health Center - Shokoshoci, Norika; Sujaya, Fista Apriani; Nasihin, Ihsan (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to determine the application of environmental accounting in waste management activities as well as the stages of accounting treatment of environmental costs by referring to PSAK 2015 No.1 carried out by the Karawang Community Health Center. The method used in this research is descriptive qualitative with a case study approach. The results of the research found that the Karawang Community Health Center had incurred costs related to waste management and had managed its waste well, namely in collaboration with third parties. However, the storage of solid or B3 waste at the Karawang Community Health Center is still not in accordance with applicable standards. And in the accounting treatment stages, the Karawang community health center has not fully carried out these stages because there is no specific presentation of environmental cost reports, therefore the Karawang community health center has not implemented environmental accounting properly. The inhibiting factors in implementing environmental accounting at the Karawang Community Health Center are HR (Human Resources), level of understanding and development.